Bacterial Bio-Resources for Remediation of Hexachlorocyclohexane - Alvarez, Analia (2012)
In the last few decades, highly toxic organic compounds like the organochlorine pesticide (OP) hexachlorocyclohexane (HCH) have been released into the environment. All HCH isomers are acutely toxic to mammals. Although nowadays its use is restricted or completely banned in most countries, it continues posing serious environmental and health concerns. Since HCH toxicity is well known, it is imperative to develop methods to remove it from the environment. Bioremediation technologies, which use microorganisms and/or plants to degrade toxic contaminants, have become the focus of interest. Microorganisms play a significant role in the transformation and degradation of xenobiotic compounds.Many Gram-negative bacteria have been reported to have metabolic abilities to attackHCH. For instance, several Sphingomonas strains have been reported to degrade thepesticide. On the other hand, among Gram-positive microorganisms, actinobacteria have a great potential for biodegradation of organic and inorganic toxic compounds. This review compiles and updates the information available on bacterial removal of HCH, particularly by Streptomyces strains, a prolific genus of actinobacteria. A brief account on the persistence and deleterious effects of these pollutant chemical is also given.